Bruegel the hand of the master : essays in context - Bruegel, Pieter de Oudere 1525-1569; Hoppe-Harnoncourt, Alice 1974-; Oberthaler, Elke; Pénot, Sabine; Sellink, Manfred 1961-; Spronk, Ron 1957- (Hannibal, 2019)
A scholarly title published to commemorate the 450th anniversary of the death of Pieter Bruegel the Elder
Colophon: "This volume of essays is published in the context of the exhibition Bruegel. The Hand of the Master (2 October 2018 to 13 January 2019, Kunsthistorisches Museum, Vienna) ... It is the result of the symposium The Hand of the Master: Materials and Techniques of Pieter Bruegel the Elder, held on 6-8 December 2018 at the Kunsthistorisches Museum."
Keywords: Bruegel, Pieter -- de Oudere -- 1525-1569; Ausstellungskatalog -- Kunsthistorisches Museum Wien -- 02.10.2018-13.01.2019 -- Wien; Konferenzschrift -- Kunsthistorisches Museum Wien -- 06.12.2018-08.12.2018 -- Wien